Anorectal Malformation: Paediatric Problem Presenting in Adult. (11th October 2015) - Chavan, Rahulkumar N.; Chikkala, Bhargav; Das, Cinjini; Biswas, Somak; Sarkar, Diptendra Kumar; Pandey, Sushil Kumar
Abstract : This is a case report of 22-year-old girl admitted with abdominal distension, vomiting, and chronic constipation since birth. Abdomen was distended, and perineal examination revealed imperforate anus with vestibular fistula (ARM). So far worldwide very few cases have been reported about anorectal malformation presenting in adulthood, and thus extremely little data is available in the literature about an ideal management of anorectal malformation in adults. In our case in the treatment instead of conventional procedure of posterior sagittal anorectoplasty (PSARP) anal transposition was done and till two years after the definitive treatment during follow-up patient has been doing well with Kelly's score of six. Our experience suggests that anal transposition provides satisfactory outcome in adults presenting late with anorectal malformation.